Cooperation and Competition in a Duopoly R&D Market - Damiano Bruno Silipo; Avi Weiss (Bar-Ilan University, Department of Economics, 2001)
In a general setting with uncertainty and spillovers in R&D activity, we consider the incentive to cooperate among firms at any or all of the following three stages. Firms can jointly agree on the level of R&D expenditures, they can set up joint research facilities, and/or they can engage in an information sharing agreements, by which they agree to share any findings with the other firm. We compare expenditures on R&D, profit levels, and welfare levels across the different possible cooperative and competitive setups and offer antitrust implications. Our model differs from previous analyses in three important ways. First, most studies consider only research aimed at lowering production costs, and therefore consider only situations where total profits fall as spillovers increase. We allow for the possibility of product innovation, and define the concepts of offsetting spillovers (falling total profits) and incremental spillovers (when total profits increase as spillovers increase). Second, we consider a wider variety of cooperation possibilities than do most prior studies. Finally, we use far more general functional forms than is usual in the literature.
Keywords: 330